Between PIAAC and the New Literacy Studies : what adult education can learn from large-scale assessments without adopting the neo-liberal paradigm (Alphabetisierung und Grundbildung, 2021)
With this book we present a selection of articles that critically deal with (internationally comparative) large-scale assessments. We acknowledge that studies such as PIAAC are often designed, financed and implemented on the basis of neo-liberal worldviews. Nevertheless, we would like to use the articles that are presented here to show the various ways in which adult and continuing education can benefit and learn from the knowledge that they generate. In PIAAC, for example, there are huge differences between the surveyed variables and the theoretical frameworks on literacies and literacy practices that the New Literacy Studies (NLS) have brought out. This book features eleven articles, which – with the NLS’s theoretical considerations and points of criticism in mind – find new and alternative evaluations and interpretations of the data. Not only can they show effects of marginalization on a large scale, but the data can also provide information about mechanisms of power in relation to literacy and basic competencies.